Comparison of the transfer accuracy of two digital indirect bonding trays for labial bracket bonding - Niu, Ye (Angle Orthod, 2021)
OBJECTIVES: To compare the transfer accuracy of two digital transfer trays, the three-dimensional printed (3D printed) tray and the vacuum-formed tray, in the indirect bonding of labial brackets. MATERIALS AND METHODS: Ten digital dental models were constructed by oral scans using an optical scanning system. 3D printed trays and vacuum-formed trays were obtained through the 3Shape indirect bonding system and rapid prototyping technology (10 in each group). Then labial brackets were transferred to 3D printed models, and the models with final bracket positioning were scanned. Linear (mesiodistal, vertical, buccolingual) and angular (angulation, torque, rotation) transfer errors were measured using GOM Inspect software. The mean transfer errors and prevalence of clinically acceptable errors (linear errors of ≤0.5 mm and angular errors of ≤2°) of two digital trays were compared using the Mann-Whitney U-test and the Chi-square test, respectively. RESULTS: The 3D printed tray had a lower mean mesiodistal transfer error (P < .01) and a higher prevalence of rotation error within the limit of 2° (P = .03) than did the vacuum-formed tray. Linear errors within 0.5 mm were higher than 90% for both groups, while torque errors within 2° were lowest at 50.9% and 52.9% for the 3D printed tray and vacuum-formed tray, respectively. Both groups had a directional bias toward the occlusal, mesial, and buccal. CONCLUSIONS: The 3D printed tray generally scored better in terms of transfer accuracy than did the vacuum-formed tray. Both types of trays had better linear control than angular control of brackets.